Microtensile bond strength of resin cements to 3-D printed and milled temporary restorative resins - Soto-Montero, Jorge; Romano, Beatriz de Cassia; Noronha, Mayara dos Santos; André, Carolina Bosso; Giannini, Marcelo (Odovtos - International Journal of Dental Sciences, 2023)
To evaluate the microtensile bond strength (µTBS) of two resin cements to 3D printed and milled CAD/CAM resins used for provisional fixed partial dentures. Blocks (5 x 5 x 5 mm) of three 3D-printed resins (Cosmos3DTemp / Yller; Resilab3D Temp / Wilcos and SmartPrint BioTemp, / MMTech) were printed (Photon, Anycubic Technology Co.). A milled material (VitaCAD-Temp, VITA) was used as control. Half the specimens were sandblasted and the rest were untreated. Two blocks were bonded with the corresponding resin cement: PanaviaV5 (Kuraray Noritake) and RelyX Ultimate (3M Oral Care). After 24 hours, the bonded blocks were sectioned into 1 x 1 mm side sticks. Half the beams were tested for µTBS and the other half was thermocycled (5000 cycles, 30s dwell-time, 5s transfer time) before µTBS testing. A four way Generalized Linear Model (material*sandblasting*cement*aging) analysis was applied. VITA exhibited the lowest µTBS, regardless of the cement, sandblasting and thermocycling. Sandblasting significantly improved the µTBS of VIT, especially after aging, but did not improve the µTBS of 3D printed resins. Sandblasting was not beneficial for 3D printed resins, although is crucial for adhesive cementation of milled temporary resins. Airborne particle abrasion affects the integrity of 3D-printed resins, without producing a benefit on the microtensile bond strength of these materials. However, sandblasting is crucial to achieve a high bond strength on milled temporary resins.